PLAY-BASED INTERVENTION TRAINING PROGRAM FOR DAYCARE WORKERS ATTENDING TO CHILDREN WITH AUTISM - Raguindin Raymond E. (Proceedings of International Conference on Special Education, 2021)
This research studied the teaching improvement of daycare workers in imitation, joint attention and language activities using the play-based early intervention training program in Cabanatuan City, Nueva Ecija. Focus group discussions were developed to explore the attitude, beliefs and practices of daycare workers. Findings of the study revealed that daycare workers have existing knowledge and experience in teaching children with Autism. Their workshops on managing inappropriate behaviors of children with Autism resulting in a general positive perception on accepting and teaching children with Autism in daycare centers. Play-based activities were modelled and participated in by daycare workers. These include demonstration, modelling, prompting and providing social reinforcers as reward. Five lectures and five training days were done to implement the training program. Daycare workers’ levels of skill in teaching imitation, joint attention and language were gathered before and after the participation in the training program. Findings suggest significant differences between pre-test and post-test scores. They have shown significant improvement in facilitating imitation, joint attention and language children with Autism after the play-based early intervention training. They were able to initiate and sustain imitation, joint attention and language activities with adequate knowledge and confidence. The following conclusions were drawn, existing attitude and beliefs greatly influenced the positive delivery mode of instruction, teacher-directed approach to improved attention, imitation, joint attention and language of children with Autism can be acquired by daycare workers and teaching skills and experience can be used as reference and basis for identifying future training needs.